Curriculum adjustment and adaptive leadership in two service-learning courses at Rhodes University as a consequence of the COVID-19 pandemic - Khuhlane, Heide Nozuko (Rhodes University, Faculty of Education, Department of Education)
The COVID-19 global pandemic altered many aspects of learning. Learning through service, a component of community engagement in higher education linking academic learning and the community was no exception. Informed by Experiential Learning Theory, this study investigated the curriculum adjustment of two service-learning courses at Rhodes University and the leadership development of those who lead the courses as a consequence of COVID-19. The study's initial goal was to highlight the position of service-learning as a component of academic learning. With the onset of the COVID-19 pandemic the goal was extended to understanding the impact of the pandemic not only on service-learning, but on leadership as well. Furthermore, the study sought to determine the responsiveness of service-learning policies at Rhodes University at a time of crisis. The study was designed as an interpretivist case study with four participants and one secondary participant. The study employed document analysis, individual interviews and a focus group interview to collect data. Data analysis took the form of content analysis and coding, through the lens of Experiential Learning Theory and an alternative service-based model. The study findings revealed that as a result of the COVID-19 global pandemic both service-learning courses had to be adapted to ensure successful completion. The adaptations included attention to scaffolded learning, assessment and course outcomes; in one course the service engagement aspect with the community was lost entirely to ensure the saftey of students through adherence to COVID-19 safety regulations. The study also found that the participants developed adaptive leadership competencies and skills, technological and collaboration skills as well as a heightened regard for pastoral care and social justice. However, it was evident that the pandemic revealed gaps in the conceptual understanding of service-learning in the context of the two courses, a need for responsive policy, and practical strategies to implement those policies in smaller units in the institution. The study thus recommends an alternative service-based model approach to service-learning, increased policy responsiveness to issues posed by the 'new normal' to support adaptive leadership development, re-defining of the university-community partnership and the identification of opportunities for innovation and collaboration intra-departmentally through service-learning.
Keywords: COVID-19 (Disease); Curriculum planning -- South Africa -- Makhanda; Rhodes University; Service learning -- South Africa -- Makhanda; Educational leadership -- South Africa -- Makhanda; Educational change -- South Africa -- Makhanda; Adaptive leadership